RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PELANGGARAN PRINSIP KEHATI-HATIAN DALAM PERBANKAN - I Nyoman Suandika (Universitas Mahendradatta, 2026)
Violation of the principle of prudence in banking has the potential to cause economic losses and weaken public trust in the financial system. So far, the repressive settlement approach has not been fully effective in creating substantive justice. This study aims to analyze the application of Restorative Justice by the Bali Police in resolving banking crimes, and to identify the factors underlying its selection. The study uses a normative-empirical method with a regulatory approach, interviews, and analysis of legal practices